Akal Budi sebagai Pilar Etika dan Spiritualitas: Telaah Filsafat Kontemporer - Agustin Nadiya Kusumawati; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2025)
This study aims to explore the urgency of reason and conscience (akal budi) in modern life through a content analysis of the Endgame podcast episode titled "Akal Budi Tidak untuk Disia-siakan" ("Reason and Conscience Are Not to Be Wasted"). The research employs a qualitative approach using content analysis and philosophical hermeneutics. The main findings reveal that akal budi is a fundamental human potential increasingly marginalized in a pragmatic and materialistic contemporary culture. The podcast invites deep reflection on how fast-paced, competitive, and technocentric modern life has diminished the contemplative spaces essential for nurturing human wisdom. Furthermore, the grounded philosophical discourse in the podcast offers a novel, accessible, and existential approach to life. The novelty of this research lies in utilizing podcast media as a contextual and spiritual source of philosophical thought. The study implies the urgency of reforming education and public discourse to foster spaces that support conscience, moral reflection, and human-centered values.